A Study of Customer Satisfaction on Online Trading System Application of Securities Company in Indonesia Using Servqual - Hery, Hery; Tarigan, Riswan Efendi (Bina Nusantara University, 2015)
The purpose of this study is to measure the service quality of online trading system implemented by PT KDB Daewoo Securities Indonesia. The study is a part of the company efforts to provide the best solution services. The study is performed to determine the influence of service quality factors on the customer satisfaction by means of ServQual method. The method takes into account five independent variables, namely, reliability (X1 ), responsiveness (X2 ), assurance (X3 ), empathy (X4 ), and tangibility (X5 ). Meanwhile, the cus- tomer satisfaction is considered as the dependent variable (Y ). The population of of the study is all 67 900 online traders at the company and the sample size is 265 traders. The data are collected via questionnaires and interviews. From the study results, we conclude that the five variables have significant influence on the customer satisfaction on the online trading system application at PT KDB Daewoo Securities Indonesia. To improve the customer satisfaction, the company should prioritize the quality- related factors, and expand and upgrade the existing facilities and infrastructures.